2015
DOI: 10.1002/2327-6924.12159
|View full text |Cite
|
Sign up to set email alerts
|

Translating research-based knowledge about infant sleep into practice

Abstract: Purpose Review infant sleep research with a focus on understanding the elements related to infant safety and infant and maternal well‐being during nighttime care. Data sources This review summarizes current research and addresses the controversies and conflicting outcomes reported in infant nighttime care. This review addresses current literature on infant sleep patterns, as well as factors that influence infant sleep and are consequences of different care routines. Conversation points are provided to help nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…The so-called typical patterns of infant sleep are sometimes over-generalized (for more detail, see Montgomery-Downs, 2008); there are currently no data upon which to base universal sleep recommendations for any age group. For example, sleep need is largely influenced by individual differences and culture (Middlemiss, Yaure, & Huey, 2015). Nonetheless, these factors conspire to make this both a rich and challenging field, which has contributed tremendously to our understanding of early development.…”
Section: Sleepmentioning
confidence: 99%
“…The so-called typical patterns of infant sleep are sometimes over-generalized (for more detail, see Montgomery-Downs, 2008); there are currently no data upon which to base universal sleep recommendations for any age group. For example, sleep need is largely influenced by individual differences and culture (Middlemiss, Yaure, & Huey, 2015). Nonetheless, these factors conspire to make this both a rich and challenging field, which has contributed tremendously to our understanding of early development.…”
Section: Sleepmentioning
confidence: 99%
“…In this final results section, we address ideas on infant sleep proffered in parenting programmes, and in particular on whether or not to leave a baby to cry. In the literature and elsewhere, this is widely referred to as infant ‘self-settling’ (Middlemiss, Yaure, and Huey, 2015), with behavioural interventions in which a crying child is gradually left alone for longer periods before being attended to described as ‘graduated extinction’ or ‘controlled crying’ (Honaker and Meltzer, 2014). Some researchers have argued that this method is effective for reducing infant sleep problems; however, they also consider that it can be emotionally challenging for parents (ibid.).…”
Section: Resultsmentioning
confidence: 99%
“…The resulting misdirection in safe sleep policy may have been overlooked initially as attention was diverted toward controversy concerning the strength of evidence for one aspect of the population-wide recommendation. For example, the recommended total bedsharing ban became a major obstacle to prevention in many countries, including the United States (Middlemiss, Yaure, & Huey, 2014), as research findings supported both (a) bedsharing as a central risk for SIDS and (b) bedsharing as a potentially safe practice contingent on factors addressed by the triple-risk model (Gordon, Rowe, & Garcia, 2015;Vennemann et al, 2012). For example, researchers reported that bedsharing was a statistically higher risk for infants exposed to cigarette smoke than for those not exposed to cigarette smoke (notably, these findings were recently replicated in New Zealand; Mitchell, Cowan, & Tipene-Leach, 2016).…”
Section: Persisting Disparitiesmentioning
confidence: 99%